Building a 3D interactive walkthrough in a digital storytelling classroom experience (Informatica, 2016)
This paper presents a real time 3D walkthrough application based on interactive VR technologies, designed and realized with and for secondary school students in order to raise their awareness about their local heritage, in particular the Medieval Walls of Grosseto, Tuscany, one of the rare examples in Italy of defensive walls remained nearly intact to this date. After detailing the learning methodology used in the classroom experiences, the paper thoroughly presents the strategy used to realize the resources needed to build the 3D model of the old town and the final application, built with an interactive digital storytelling approach.